Cell Banking of hiPSCs: A Practical Guide to Cryopreservation and Quality Control in Basic Research. (21st September 2020) - Shibamiya, Aya; Schulze, Elisabeth; Krauß, Dana; Augustin, Christa; Reinsch, Marina; Schulze, Mirja Loreen; Steuck, Simone; Mearini, Giulia; Mannhardt, Ingra; Schulze, Thomas; Klampe, Birgit; Werner, Tessa; et al.
Abstract: The reproducibility of stem cell research relies on the constant availability of quality‐controlled cells. As the quality of human induced pluripotent stem cells (hiPSCs) can deteriorate in the course of a few passages, cell banking is key to achieve consistent results and low batch‐to‐batch variation. Here, we provide a cost‐efficient route to generate master and working cell banks for basic research projects. In addition, we describe minimal protocols for quality assurance including tests for sterility, viability, pluripotency, and genetic integrity. © 2020 The Authors. Basic Protocol 1 : Expansion of hiPSCs Basic Protocol 2 : Cell banking of hiPSCs Support Protocol 1 : Pluripotency assessment by flow cytometry Support Protocol 2 : Thawing control: Viability and sterility Support Protocol 3 : Potency, viral clearance, and pluripotency: Spontaneous differentiation and qRT‐PCR Support Protocol 4 : Identity: Short tandem repeat analysis